2008
DOI: 10.3748/wjg.14.1622
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocirrhosis in a pancreatic cancer patient with liver metastases: A case report of complete resolution of pseudocirrhosis with an early recognition and management

Abstract: We report a case of pseudocirrhosis arising in the setting of regression of liver metastases from pancreatic cancer. A 55-year-old asymptomatic woman presented to our clinic with newly diagnosed metastatic pancreatic cancer with extensive liver metastases. She underwent systemic chemotherapy with gemcitabine and oxaliplatin (GEMOX). After 8 cycles of therapy, she had a remarkable response to the therapy evidenced by decline of carcinoembryonic antigen (CEA) and CA19 by > 50% and nearly complete resolution of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…In the present case, the patient survived after severe regorafenib-induced hepatic injury. The course of treatment in the present as well as another case (12) suggests that pseudocirrhosis with a mild elevation of aminotransferase levels during chemotherapy may be reversed by discontinuation of the chemotherapeutic agents. In such cases, where the chemotherapeutic agents administered are potent enough to induce liver injury and reversible pseudocirrhosis, potent antitumor effects may also be expected.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In the present case, the patient survived after severe regorafenib-induced hepatic injury. The course of treatment in the present as well as another case (12) suggests that pseudocirrhosis with a mild elevation of aminotransferase levels during chemotherapy may be reversed by discontinuation of the chemotherapeutic agents. In such cases, where the chemotherapeutic agents administered are potent enough to induce liver injury and reversible pseudocirrhosis, potent antitumor effects may also be expected.…”
Section: Discussionsupporting
confidence: 50%
“…Although the precise mechanism underlying the development of pseudocirrhosis remains unknown, the response to systemic chemotherapeutic agents may induce cirrhotic changes with tumor shrinkage following chemotherapy. Previous reports (10)(11)(12) have indicated that pseudocirrhosis may be associated with nodular regenerative hyperplasia (NRH) caused by chemotherapy-induced hepatic injury. NRH is characterized by widespread transformation of nor mal liver parenchyma into hyperplastic regenerative nodules without bridging fibrosis, a characteristic that distinguishes this entity from liver cirrhosis (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently reported cause of pseudocirrhosis is metastatic breast cancer treated with chemotherapy [4][5][6][7][8][9][10][11][12][13][14] , which commonly presents with diffuse nodular changes of the liver surface on ct imaging 15 . However, the liver can also become nodular and resemble cirrhosis after hepatic metastasis in pancreatic, esophageal, and small-cell lung cancer [16][17][18] . To our knowledge, pseudocirrhosis has not been reported in metastatic mtc.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Sinusoidal dilatation is a common adverse event with oxaliplatin that can cause noncirrhotic portal hypertension in patients with stage iii or iv colorectal cancer 21,22 . In a report of pseudocirrhosis in the setting of metastatic pancreatic cancer, the liver appeared normal after discontinuation of gemcitabine and oxaliplatin, but that change was also accompanied by primary tumor regression and reduction in the CA19-9 tumour marker, suggesting that metastatic disease may have 16 . In general, there is little to no evidence that adverse effects from folfox can mimic cirrhosis.…”
Section: Toxicities Of Folfox and Sunitinibmentioning
confidence: 99%